Critical behavior of the van der Waals bonded high T C ferromagnet Fe3GeTe2 - Bingjie Liu; Youming Zou; Shiming Zhou; Lei Zhang; Zhe Wang; Hexuan Li; Zhe Qu; Yuheng Zhang (Scientific Reports, 2017)
Abstract Fe3GeTe2 is a promising candidate for van der Waals bonded ferromagnet because of its high Curie temperature and the prediction that its ferromagnetism can maintain upon exfoliating down to single layer. Here, we have reported the critical behavior to understand its ferromagnetic exchange. Based on various techniques including modified Arrott plot, Kouvel-Fisher plot, and critical isotherm analysis, a set of reliable critical exponents (β = 0.327 ± 0.003, γ = 1.079 ± 0.005, and δ = 4.261 ± 0.009) has been obtained. The critical behavior suggests a three-dimensional long-range magnetic coupling with the exchange distance decaying as J(r) ≈ r −4.6 in Fe3GeTe2. The possible origin of three-dimensional magnetic characteristics in van der Waals bonded magnets is discussed.